Organic Single‐Crystalline Semiconductors for Light‐Emitting Applications: Recent Advances and Developments. Issue 10 (10th September 2019) - Ding, Ran; An, Ming‐Hui; Feng, Jing; Sun, Hong‐Bo
Abstract: Organic single‐crystalline semiconductors (OSCSs), as a vital branch of organic semiconductors, have recently attracted intense interest due to their numerous advantages such as highly ordered structure, high carrier mobility, high thermal stability, and low impurity levels, and they have worldwide use in different kinds of applications. In particular, the nature of better luminescence properties and remarkable charge‐transport characteristics is a prerequisite for light‐emitting aspects. Here, a concise overview of the recent progress on OSCSs research is provided, highlighting the prominent properties of OSCSs which are pertinent to light‐emitting behavior. Various crystal‐growth strategies are surveyed for the preparation of high‐quality OSCSs via solution, melting, and vapor phases. Two typical electrical‐pumping light‐emitting devices, including organic light‐emitting transistors and organic light‐emitting diodes, are summarized with recent advances and developments exhibiting the latent potentialities of OSCSs in optoelectronics. Abstract : Recent advances and developments in organic single‐crystalline semiconductors in terms of their optoelectronic properties for their light‐emitting aspects, crystal‐growth strategies for high‐quality crystals, and two typical light‐emitting devices are reviewed. The nature of the better luminescence properties and remarkable charge‐transport characteristics for light‐emitting applications is summarized, and their thorough understanding is the key factor to the material functionalization.